Antioxidant and Anti-Inflammatory Activities of Kecombrang (Etlingera elatior) Extracts: A Systematic Literature Review - Pribadi, Fajar Wahyu; Robbani, Muhammad Izzulfahmi; Salsabila, Chasna; Alifia, Carrissa; Kanti, Kanaya Adhira; Akbar, Vania Nafiisa; Andini, Sofia Dewi; Firdaus, Naila Asy Syifa; Arrasyi, Alifah Putri Nur; Adiwijaya, Kharisma (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Kecombrang (Etlingera elatior) is a plant commonly used in traditional medicine and as a food seasoning by the Indonesian community. It contains various secondary metabolites such as saponins, tannins, alkaloids, steroids, flavonoids, and phenolic compounds, which are distributed from its rhizomes to its flowers. This literature review aims to provide a deeper understanding of the active compounds in kecombrang and their potential health benefits for humans. The study was conducted as a literature review using the PRISMA method, with data sources from four major databases: ScienceDirect, PubMed, Scopus, and Google Scholar. Findings from several studies involving rats as test subjects indicate that the active compounds in kecombrang exhibit antioxidant effects that protect cells from oxidative damage. Additionally, kecombrang extract demonstrates anti-inflammatory activity by directly inhibiting the enzymes COX and lipoxygenase, thereby reducing the biosynthesis of prostaglandins and leukotrienes.